Satisfacción de los usuarios frente a la calidad de la atención prestada en el programa de odontología integral del adolescente y ortodoncia, 2001 (2004)
ABSTRACT: Over the last few years the topic of quality of care in health services in Colombia has raised enormous interest through laws established by the Mandatory System of Warranty in Quality, and particularly within our college by the adoption of the teaching-service model which looks for a comprehensive training of its students. This is about looking at quality not only from the merely technical and scientific point of view, but also integrating other aspects such as personal relationships. A study was done with the purpose of determining the quality of care under this dimension, in which the degree of satisfaction after a service was provided, was measured identifying the critical factors of this service. It was found that the 320 people who used the orthodontic service are a homogeneous population with a degree of satisfaction based upon multifactorial reasons depending on the patient-orthodontist-institution relationship. Also, it was found that the geographical location of the college was important, but, the functional accessibility was difficult due to long waiting periods of time to get an appointment, lack of administrative control, and deficiencies in information given to the public; it is equally important to identify and control the factors that made the treatments longer than necessary. These results will allow us to improve the quality of care, the service to the public, and the formative process of our graduated professionals.